Role of microRNAs in cardiac hypertrophy, myocardial fibrosis and heart failure - De-li Dong; Bao-feng Yang (Elsevier, 2011)
MicroRNAs (miRNAs) are endogenous small non-coding RNA molecules that post-transcriptionally regulate gene expression. MiRNA expression and function in heart disease remain to be determined but modulation of miRNA expression in vivo has revealed that miRNAs play an important role in controlling heart function and structure. In fact, abnormal expression of miRNAs may initiate and contribute to the progress of heart disease. Here, we summarize the literature relating to the involvement of miRNAs in cardiac hypertrophy, myocardial fibrosis and heart failure.